Long-term Supplementation Affects the Production, Composition and Lactation Curve of Local Grazing Goats - Maldonado-Jáquez, Jorge Alonso; Torres-Hernández, Glafiro; Hernández-Mendo, Omar; Gallegos-Sánchez, Jaime; Mora-Flores, José Saturnino; Granados-Rivera, Lorenzo Danilo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Twenty-four local goats were divided into two treatments: 1) control group fed only on grazing, and 2) supplemented group, which received supplemental feeding before parturition and during lactation. The highest values of milk production per goat, total milk production, days in milk production fat, protein and lactose yield per day were observed in goats of the supplemented treatment. No treatment effect was found for peak lactation production, persistence of peak production, duration of peak lactation production phase, total yield and fat, protein and lactose concentration, nor for milk production per goat, total milk production and days in milk production by type of calving (single or double). Wood’s curve parameters had the lowest standard error of the estimator in control group, but the highest values of the estimator in supplemented group. We concluded that long-term dietary supplementation of local goats in northern Mexico increases milk production and milk protein, fat and lactose. In addition, it positively influences the estimation of lactation curve parameters. Highlights: The utilization of totally mixed diets as a supplementation strategy in grazing goats has been demonstrated to enhance milk production. Long-term supplementation has been shown to exert a beneficial influence on the estimation of lactation curve parameters. Furthermore, long-term supplementation has been observed to elevate productivity in Criollo goats from northern Mexico.